Vascular endothelial growth factor-receptor 1 inhibition aggravates diabetic nephropathy through eNOS signaling pathway in db/db mice. - Keun Suk Yang (Public Library of Science (PLoS), 2014)
The manipulation of vascular endothelial growth factor (VEGF)-receptors (VEGFRs) in diabetic nephropathy is as controversial as issue as ever. It is known to be VEGF-A and VEGFR2 that regulate most of the cellular actions of VEGF in experimental diabetic nephropathy. On the other hand, such factors as VEGF-A, -B and placenta growth factor bind to VEGFR1 with high affinity. Such notion instigated us to investigate on whether selective VEGFR1 inhibition with GNQWFI hexamer aggravates the progression of diabetic nephropathy in db/db mice. While diabetes suppressed VEGFR1, it did increase VEGFR2 expressions in the glomerulus. Db/db mice with VEGFR1 inhibition showed more prominent features with respect to, albuminuria, mesangial matrix expansion, inflammatory cell infiltration and greater numbers of apoptotic cells in the glomerulus, and oxidative stress than that of control db/db mice. All these changes were related to the suppression of diabetes-induced increases in PI3K activity and Akt phosphorylation as well as the aggravation of endothelial dysfunction associated with the inactivation of FoxO3a and eNOS-NOx. In cultured human glomerular endothelial cells (HGECs), high-glucose media with VEGFR1 inhibition induced more apoptotic cells and oxidative stress than did high-glucose media alone, which were associated with the suppression of PI3K-Akt phosphorylation, independently of the activation of AMP-activated protein kinase, and inactivation of FoxO3a and eNOS-NOx pathway. In addition, transfection with VEGFR1 siRNA in HGECs also suppressed PI3K-Akt-eNOS signaling. In conclusion, the specific blockade of VEGFR1 with GNQWFI caused severe renal injury related to profound suppression of the PI3K-Akt, FoxO3a and eNOS-NOx pathway, giving rise to the oxidative stress-induced apoptosis of glomerular cells in type 2 diabetic nephropathy.